2015
DOI: 10.1118/1.4906241
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of RACT for 3D dose measurement and range verification in a water phantom

Abstract: This study demonstrates that computed tomographic scanner based on ionizing radiation-induced acoustics can be used to verify dose distribution and proton range with centi-Gray sensitivity. Realizing this technology into the clinic has the potential to significantly impact beam commissioning, treatment verification during particle beam therapy and image guided techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Studies by Jones et al and Alsanea et al indicate that Bragg peak localization with about 1-mm precision may be possible. 12,13 These studies also showed that the use of multiple ultrasound detectors may reconstruct a tomographic image of the proton dose distribution.…”
Section: Introductionmentioning
confidence: 95%
“…Studies by Jones et al and Alsanea et al indicate that Bragg peak localization with about 1-mm precision may be possible. 12,13 These studies also showed that the use of multiple ultrasound detectors may reconstruct a tomographic image of the proton dose distribution.…”
Section: Introductionmentioning
confidence: 95%
“…Hayakawa et al detected acoustic pulse signals in animal tissues and humans, demonstrating the feasibility of determining dose distribution in proton therapy . A 3D dosimetric scanner based on ionizing radiation‐induced acoustic computed tomography (RACT) was theoretically designed to verify dose distribution and proton range in a water phantom . A clinical ultrasound array was deployed to localize the proton Bragg peak from reconstructed thermoacoustic images in water and gelatin phantoms, which provided perfectly co‐registered overlay of the Bragg peak onto a standard ultrasound image acquired by the same ultrasound array, and overcame the presence of acoustic heterogeneity and speed of sound errors …”
Section: Introductionmentioning
confidence: 99%
“…Alsanea et al proposed radiation-induced acoustic computed tomography (RACT) in which the proton-induced acoustic signal measured by an array of transducers is used to reconstruct the 3D dose distribution through a filtered backprojection algorithm. 31,58 The reconstruction accuracy of clinical pencil beam dose depositions was investigated as a function of noise level and number of projection angles. For low noise levels (approximately equal to the maximum signal pressure amplitude), RACT showed sub-millimeter proton range verification and <2% dosimetric Bragg peak accuracy.…”
Section: B Recent Workmentioning
confidence: 99%